Pendekatan Komunikatif Dalam Pembelajaran Bahasa Arab Untuk Penutur Asing - Fauziah Bachtiar (CV. SINAR HOWUHOWU, 2026)
Arabic language learning for foreign speakers (Arabic as a Foreign Language) has experienced significant development in line with the increasing demands of global, academic, and religious communication. However, the practice of Arabic language instruction is still often dominated by structural approaches that focus on the mastery of grammatical rules, resulting in the underdevelopment of learners’ communicative competence. This article aims to examine the concepts, characteristics, implementation, advantages, and challenges of the communicative approach in teaching Arabic to foreign language learners. This study employed a library research method by collecting and analyzing various scholarly sources, including books, journal articles, and relevant research findings published within the last five years. The findings indicate that the communicative approach views language as a tool for communication used in real-life contexts, thereby orienting the learning process toward the development of communicative competence through interaction, collaboration, and authentic language use. This approach has been proven to enhance speaking and listening skills, self-confidence, learning motivation, and active learner participation. Nevertheless, its implementation still faces several challenges, such as limited language environments, teachers’ competencies, and the availability of supportive instructional media. Therefore, the communicative approach can serve as an effective alternative in teaching Arabic to foreign language learners when supported by contextual instructional design and a conducive language environment.